The use of SIG in studying the effect of the characteristics of playing equipments on the children’s playing methods: Case of Ben Boulaid Square – Batna - Boukhetache , Besma; Dib, Belkacem (Journal of Architecture and environment of child, 2023)
Play is the dominant characteristic of children and the characteristic of them, so we decided in this study to research the design criteria for play equipment in Ben Boulaid Square in the city of Batna and its impact on the way children play, and access to the physical characteristics of these equipment that contribute positively to children’s play. In this study, we relied on the analytical approach of the behavioral maps that we drew using the geographic information systems method and monitoring the information from its source through the observation technique. The study concluded that the physical characteristics of the playing equipment in the Ben Boulaid Corridor Square contribute positively rather than negatively to the way children play within the field value (9.83-24.45).